Thioglycolic acid modified chitosan: a template for in-situ synthesis of CdSe QDs for cell imaging. Issue 10 (2nd October 2020) - Kumar, Hridyesh; Dutta, P. K.; , Sushma
Abstract: We prepared CdSe QDs on thioglycolic acid modified chitosan (CdSe@Chit-TGAc). It showed bright yellow fluorescence under long wave UV radiation. Optical properties and growth of crystal was checked by ultraviolet-visible spectroscopy and photoluminescence spectroscopy. HRTEM and XPS results demonstrated that CdSe QDs were successfully prepared and decorated on thiol modified chitosan templet and size of CdSe QDs was also successfully stabilized within the quantum dot size range. Biocompatibility of CdSe@Chit-TGAc was checked on in-vitro system in two cell lines i.e., normal lung cell line (WI-38) and pulmonary cancerous cell line (A549) which exhibited significant uptake and florescence of CdSe@Chit-TGAc with WI-38. The concentration-dependent cytotoxicity in A549 cells for the QDs was also studied. Based on preliminary bioassays, further mechanistic studies can be done to exploit the properties of CdSe@Chit-TGAc as fluorescent agent for cell imaging, targeted drug delivery, nano-medicine etc. GRAPHICAL ABSTRACT: